Sistem Keamanan Pintu Rumah Berbasis Internet of Things Dengan Sensor Reed Switch dan Telegram - Zulkam Sopalatu; Endang Retnoningsih; Syahbaniar Rofiah; Yunus Fadhillah Soleman (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2026)
Home security is an important aspect that requires special attention. This research aims to design and implement a Reed Switch sensor-based home door security system with notification via telegram. This system uses NodeMCU ESP8266 as a microcontroller, magnetic Reed Switch sensor to detect door status, and supporting devices such as LED, buzzer, and telegram application as notification media. The system development method involves hardware design, software programming, with functional testing of the system. The test results show that the system can accurately detect changes in door status (open and closed) and send real-time notifications to users via telegram. The implementation of this system is expected to enhance home security by providing early warning to users.